Young people’s participation experiences of technical and vocational education and training interventions in low- and middle-income countries: a systematic review of qualitative evidence - Yi Shi; Mukdarut Bangpan (Empirical Research in Vocational Education and Training, 2022)
Abstract Technical and vocational education and training (TVET) has attracted wide attention with its potential to alleviate poverty and improve youth employment in low- and middle-income countries (LMICs). However, no agreement has been reached on its impact on participants’ wellbeing and livelihoods. Most previous reviews were restricted to economic and employment-related outcomes through statistical meta-analyses and failed to examine participants’ comprehensive experiences. This systematic review investigated young people’s learning process and consequences of TVET participation in LMICs by reviewing qualitative evidence across 31 published and unpublished studies from 2000 to 2019. Adopting a framework thematic synthesis approach, this study revealed that TVET participation had a multi-dimensional impact on young people’s cultural capital (skills and knowledge, credentials and socio-emotional competencies), social capital (bonding, bridging and linking social relationships), aspirations, and health, beyond economic consequences. Participants’ mixed experiences were collectively shaped by multiple factors, including intervention features, intervention quality (curriculum and content, instructor and instruction, administration and management), learning environment (physical environment, instructor-learner relationship and peer relationship), individual characteristics, and social norms. Findings also indicated that disadvantaged youth particularly benefitted from TVET participation, which highlighted the potential of TVET to improve education access and equity. A framework was distilled from evidence synthesis to inform future research and practice that aim to design, implement and evaluate TVET in a way to enhance young people’s overall wellbeing in the developing context.